The Role of Teachers in Using Educational Game Tools at Ar-Rahmat PAUD, Percut Sei Tuan District - Malika, Tri Ninda; Lubis, Mayang Sari; Siregar, Asrul (Holistic Science, 2024)
The existence of PAUD or pre-school education is increasingly needed in society. This is especially true because of the current rapid population growth, which causes demands to provide the best educational institutions for children. PAUD is an education given to children aged 0 to 6 years in helping their growth and development to enter the next level of elementary school education. In this case, teachers have a very important role for children because they function as examples or role models for children. In the learning process, teachers are the ones who can organize effective learning and adjust it to the stages of child development. The learning process will be interesting if learning resources and media are used correctly according to the learning design. The purpose of this study was to determine the role of PAUD teachers in the use of APE and identify the impact of using APE on child development in PAUD, as well as to determine the difficulties faced by PAUD teachers when using APE as a learning aid. This study uses a qualitative approach, and looks at how PAUD teachers use APE in early childhood education institutions (especially in PAUD Ar-Rahmat). The data collection techniques used by researchers were by using observation, interview, and documentation techniques. The results of the study show that PAUD teachers play a very important role in selecting, designing, and integrating APE into the learning process, which has a positive impact on child development.